“Aik Chadir Maili Si” and Baidi’s Feminism Consciousness - Razzaq, Shireen; Ikram, M.; Nazir, Nouman (sourcecoder, 2022)
Aik Chaddar Malli Si"is an important creation in Urdu beautifully portrayed social and domestic problems of fiction….. has women. Under the influence of this novel and Punjabi and Hindustani comes across with their many social depiction of female characters we psychological condition. In novel; Female characters domestic and seems the victim of social discard. She seems fighting with social chauvinism. Novel envisage feminism wich norms. She is victim of will be surface of this article.